Growth and luminescent properties of TbAlO3 - Zorenko, Yu.; Gorbenko, V.; Vozniak, T.; Batentschuk, Miroslaw; Osvet, Andres; Winnacker, Albrecht; et al. (physica status solidi (a), 2010)
The paper is dedicated to the investigation of growth processes by liquid phase epitaxy (LPE) and the luminescent properties of single-crystalline films (SCFs) of TbAlO_3 terbium-aluminum perovskite (TbAP) perovskite doped with manganese ions. We found that the Mn2+ and Mn3+ or even Mn5+ states can occur in TbAP:Mn SCF depending on the concentration of manganese ions in the 0.01–1.1 at.% range. The Mn2+ ions in TbAP host possess orange luminescence in the band peaked at 572 nm with a lifetime of 1.24 ms at 300 K that is caused by the ^4T1 i̊ghtarrow6 A1 radiative transitions. The cascade energy-transfer processes can be realized in TbAP:Mn SCF: (i) from 5d–4f states of Tb3+ cations to Mn2+ ions; (ii) from Mn2+ ions to 4f states of Tb3+ cations. The latest process strongly decreases the efficiency of Mn2+ luminescence in TbAlO_3 perovskite with respect to the Tb_3Al5O12 garnet host.
EAM Import::2019-03-13